Patriarchy Canonization: Comparing Women's Political Participation in Matrilineal and Patrilineal Orders in Sumatra, Indonesia. - Erond Litno Damanik (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
The purpose of this study is to describe a recent comparison of women's political participation based on empirical evidence on the matrilineal and patrilineal orders in West and North Sumatra, respectively. This study was motivated by the low involvement of women in politics in the 2014 and 2019 general elections. The study offers specific insights into kinship order as political allegiance. This is a qualitative research carried out using a pragmatic methodological approach with academic discussions directed at the relationship between kinship and political participation. The results showed that the canonization of Islamic patriarchy in the matrilineal order impacts involution and exclusive women in the domestic arena. Meanwhile, the canonization of Christian patriarchy in the patrilineal order impacts devolution and inclusive women in politics. Therefore, based on this empirical evidence, it is concluded that the kinship system is not a relevant political allegiance.